3x+7-2(x+9)=4

Simple and best practice solution for 3x+7-2(x+9)=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+7-2(x+9)=4 equation:


Simplifying
3x + 7 + -2(x + 9) = 4

Reorder the terms:
3x + 7 + -2(9 + x) = 4
3x + 7 + (9 * -2 + x * -2) = 4
3x + 7 + (-18 + -2x) = 4

Reorder the terms:
7 + -18 + 3x + -2x = 4

Combine like terms: 7 + -18 = -11
-11 + 3x + -2x = 4

Combine like terms: 3x + -2x = 1x
-11 + 1x = 4

Solving
-11 + 1x = 4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 1x = 4 + 11

Combine like terms: -11 + 11 = 0
0 + 1x = 4 + 11
1x = 4 + 11

Combine like terms: 4 + 11 = 15
1x = 15

Divide each side by '1'.
x = 15

Simplifying
x = 15

See similar equations:

| 8r-50-24r=-41+r | | 1+.5t=3 | | y-55=-2(x-5) | | 36y=35y-10 | | 4x^2+4x-11=0 | | wat=water | | 4x^2+7XY+3Y^2=0 | | water=hi | | 3y=3x-13 | | 11-2(8+3p)=7(7) | | 5x+25(x-4)=170 | | 7x+27=125 | | 5x+25(9-4)=170 | | +4/-2=7 | | 7x+3=-14 | | 9*x-7x= | | 0.9(5x+15)=2.2-(x+3) | | 56x^2-18x=0 | | 0.25(b+6)=12 | | 5y+7y=12 | | 6x^2+3x+3=0 | | 6x^2+3x-8=0 | | 3(q-3)+4q-1=4q+5+3q | | y-22=-1(x-4) | | 3(x+1)-8=50 | | (50-x)/3=16 | | 4x+60=17 | | 6q-4=3q+8 | | -3(6P+6)-2(4-17P)=3(7+5P) | | 17+x=60 | | 16x+8=4x-8 | | w(w+5)=104 |

Equations solver categories